(NiZ pOLX[I W gERMANI@s [(NAWTOTURIZM(B]s - (NiWANOW(B,(Ns(B.s (NsERGEJs (2017)
(Nw RAMKAH PROEKTA (B"(NoSENX(B. (NbEZ WIZ(B" (NPUTE[ESTWIE NA AWTOMOBILQH (BRavon (NPO DOROGAM eWROPY(B, (N^TOBY LU^[E UZNATX MESTNYE OSOBENNOSTI I N@ANSY AWTOTURIZMA(B.s
Keywords: (Nturizms; (Npute{estwies